Natural scene statistics of color and range - Che-Chun Su; Bovik, A. C.; Cormack, L. K. (2011 18th IEEE International Conference on Image Processing, 2011)
Color and depth play important roles in natural scenes and in vision, and their perception is related. Extensive work has been conducted on studying the luminance statistics of natural scenes; however, there is very little work done on analyzing the statistics between luminance and range in natural scenes, not to mention color and range. In this paper, we present the LIVE Color+3D Database, which contains 12 sets of color images with corresponding ground truth range maps in a high-definition resolution of 1280×720. We examined the statistical distribution of range gradients conditioned on the Gabor responses of the color images, as well as the variations of statistical measures of range gradients with changes in the Gabor responses. The analysis results show that the distributions of range gradients conditioned on the Gabor responses have very similar exponential shapes for both luminance and chrominance channels. Moreover, we also found that the depth difference between neighboring pixels increases as the corresponding magnitudes of the Gabor responses rise.